I believe that examples 2 and 3 had typos, and I can't figure out the second column of example 3.

**tl;dr - I think the second columns were included by mistake.**

### Example 2

```
Input: "F?1:T?4:5"
Output: "4"
Explanation: The conditional expressions group right-to-left. Using parenthesis, it is read/evaluated as:
"(F ? 1 : (T ? 4 : 5))" "(F ? 1 : (T ? 4 : 5))"
-> "(F ? 1 : 4)" or -> "(T ? 4 : 5)"
-> "4" -> "4"
```

I think the top line of column 2 should read:

```
"((F ? 1 : T) ? 4 : 5)"
```

in order to get the next line in that column.

### Example 3

```
Input: "T?T?F:5:3"
Output: "F"
Explanation: The conditional expressions group right-to-left. Using parenthesis, it is read/evaluated as:
"(T ? (T ? F : 5) : 3)" "(T ? (T ? F : 5) : 3)"
-> "(T ? F : 3)" or -> "(T ? F : 5)"
-> "F" -> "F"
```

Again, I think that the top line of column 2 is a typo (it repeats the top line of column 1). Regardless, however, I don't see how it's possible to get the next line of column 2 at all. Does anyone see it?

In any case, I thought that **"conditional expressions group right-to-left"** was to avoid ambiguity. If, on the other hand, that rule still allows for some ambiguity (I don't think it does), can one prove that the answer is always the same?

...or maybe I'm missing something obvious!